A Novel Role of VEGFC in Cerebral Ischemia With Lung Injury - Wen, Mu-Dong; Jiang, Ya; Huang, Jin; Al-Hawwas, Mohammed; Dan, Qi-Qin; Yang, Rui-An; Yuan, Bing; Zhao, Xiao-Ming; Jiang, Ling; Zhong, Ming-Mei; Xiong, Liu-Lin; Zhang, Yun-Hui (Frontiers in Neuroscience, 2019)
Cerebral ischemia (CI) is a severe brain injury resulting in a variety of motor impairments combined with secondary injury in remote organs, especially the lung. This condition occurs due to insufficient blood supply to the brain during infancy. However, it has a molecular linkage that needs to be thoroughly covered. Here, we report on the role of vascular endothelial growth factor C (VEGFC) in lung injury induced by CI. The middle cerebral artery occlusion (MCAO) was depended to establish the animal model of CI. Rats were used and brain ischemia was confirmed through TTC staining. Serum was used for protein chip analysis to study the proteomic interaction. Immunohistochemistry analyses were used to quantify and locate the VEGFC in the lung and brain. The role of VEGFC was detected by siVEGFC technology in SY5Y, HUCEV and A549 cell lines, under normal and oxygen glucose deprivation (OGD) conditions in vitro. As a result, the TTC staining demonstrated that the model of brain ischemia was successfully established, and MPO experiments reported that lung damage was induced in MCAO rats. VEGFC levels were up-regulated in serum. On the other hand, immunohistochemistry showed that VEGFC increased significantly in the cytoplasm of neurons, the endothelium of small trachea and the lung cells of CI animals. On a functional level, siVEGFC effectively inhibited the proliferation of SY5Y cells and decreased the viability of HUVEC cells in normal cell lines. But under OGD conditions, siVEGFC decreased the growth of HUVEC and increased the viability of A549 cells, while no effect was noticed on SYSY cells. Therefore, we confirmed the different role of VEGFC played in neurons and lung cells in cerebral ischemia-reperfusion injury. These findings may contribute to the understanding the molecular linkage of brain ischemia and lung injury, which therefore provides a new idea for the therapeutic approach to cerebral ischemia-reperfusion.